2012
DOI: 10.1007/s10549-012-2265-4
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic model of early breast cancer relapse after standard adjuvant therapy and comparison with metastatic disease on initial presentation

Abstract: Breast cancer can metastasize at any time during its course, but timing of systemic relapse cannot be predicted by traditional TNM staging. Characteristics of distant recurrence within the first 3 years of diagnosis may identify a group of patients who could benefit from novel strategies to prevent systemic relapse. Of 1,089 patients with breast cancer treated at our institution between January 2007 and May 2011, we identified 76 with de novo metastases (on presentation) and 40 with systemic relapse after a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
5
9
0
Order By: Relevance
“…There are few studies reporting PR-negative staining as an independent factor for breast cancer poor prognosis. Only Chen et al (24) suggested that no PR expression was an independent factor for the early recurrence of breast cancer, which is consistent with the present results. However, PR-negative patients include patients with certain triple-negative cancers, which may cause this difference.…”
Section: Discussionsupporting
confidence: 93%
“…There are few studies reporting PR-negative staining as an independent factor for breast cancer poor prognosis. Only Chen et al (24) suggested that no PR expression was an independent factor for the early recurrence of breast cancer, which is consistent with the present results. However, PR-negative patients include patients with certain triple-negative cancers, which may cause this difference.…”
Section: Discussionsupporting
confidence: 93%
“…According to previous studies, de novo Stage IV disease seemed to show a favorable biological profile, since they were more likely to be low‐grade tumors with positive hormone receptors when compared with relapsed BC . Conversely, our data suggested that de novo Stage IV disease expresses a more aggressive phenotype compared to earlier stages, characterized by high‐grade tumors, negative hormone receptors, high Ki67 proliferation rate, and positive HER2 status.…”
Section: Discussionsupporting
confidence: 58%
“…According to previous studies, de novo Stage IV disease seemed to show a favorable biological profile, since they were more likely to be low-grade tumors with positive hormone receptors when compared with relapsed BC. 12,13 Conversely, our data suggested that de novo Stage IV disease expresses a more aggressive phenotype compared to earlier stages, characterized by high-grade tumors, negative hormone receptors, high Ki67 proliferation rate, and positive HER2 status. This could mean that de novo metastatic BC represents a gradual evolution of early BC from good toward poor prognostic factors, whereas relapsed tumors are characterized by a poor prognostic profile since the beginning.…”
Section: Discussionmentioning
confidence: 61%
“…Another study that investigated the Ki-67 status during endocrine therapy revealed that Ki-67 was reduced to a greater extent in PgRpositive cancers when compared with PgR-negative cancers [16], suggesting that treating PgR-negative cancers with hormonal therapy could not completely prevent cancer cell activation. Other researchers showed that a PgRnegative status was an important contributor to the relapse risk in early [17] and late periods [18]. The same result was published for metastatic breast cancer.…”
Section: Discussionsupporting
confidence: 56%